Live yeast culture and monensin in high grain diets for cattle: rumen fermentation and “in situ” degradability Leveduras vivas e monensina em dietas de alto concentrado para bovinos: parâmetros ruminais e degradabilidade "in situ" - José Carlos Machado Nogueira Filho; Luis Carlos Vinhas Ítavo; Maria Tereza Antunes; Rodrigo da Costa Gomes; Paulo Roberto Leme (Revista Brasileira de Saúde e Produção Animal, 2010)
Live yeast cultures have been used as an alternative to replace antibiotics in diets for ruminants. Therefore, the aim was to evaluate the effects of adding live yeast culture (Saccharomyces cerevisiae, Beef Sacc®, Alltech, Inc.), monensin (Rumensin®, Elanco, Inc.) and the combination of both additives in high grain diets, on rumen fermentation patterns, protozoa organisms and in situ degradability of diet components. Four rumen-cannulated steers were fed a basal ration (2.8Mcal ME/kg DM, 14% CP) and submitted to one of four treatments following a 4x4 Latin Square design: control (CON, no additives), yeast (YEA, 0.6g/kg of dry matter), monensin (MON, 0.3g/kg of dry matter) and monensin plus yeast (MON+YEA). After 14 days of diet adaptation, the rumen fermentation parameters, the protozoa numbers and the degradation kinetics of corn (CO), soybean meal (SM) and soybean hulls (SH) were assessed. Feed additives did not affect rumen pH, butirate and ammonia nitrogen concentrations, but decreased total short chain fatty acids (mM). MON and MON+ YEA decreased acetate (%) and acetate:propionate ratio whereas propionate was increased by MON and MON+YEA at all sampling times, and by YEA at 4 and 6h post-feeding only. YEA increased the number of protozoa whereas MON and MON+YEA inhibited those microorganisms (total organisms [x104/mL]). There were no effects of YEA and MON+YEA on in situ degradability parameters of any evaluated feed, however, MON increased NDF degradation rate of SH. Monensin effects on rumen fermentation are more significant than those observed when feeding live yeast cultures, and the combination of both additives does not improve their effects. Leveduras têm sido utilizadas para substituir antibióticos em dietas para ruminantes. Assim, objetivou-se avaliar o efeito de leveduras vivas (Saccharomyces cerevisiae, Beef-Sacc®, Alltech, Inc.), monensina (Rumensin®, Elanco, Inc.) e a combinação de ambos em dietas com alto concentrado, sobre a fermentação, os protozoários e a degradação ruminal in situ. Quatro novilhos Nelore canulados no rúmen foram alimentados com uma dieta base (2,8Mcal EM/kg de matéria seca [MS]; 14% PB) e submetidos, de acordo com um delineamento Quadrado Latino 4x4, aos tratamentos: controle (CON; sem aditivos), levedura (LEV; 0,6 g/kg de MS), monensina (MON; 0,3g/kg de MS) e monensina mais levedura (MON+LEV). Avaliou-se os números de protozoários e os parâmetros de fermentação ruminal e de degradação do milho (MI), farelo de soja (FS) e casca de soja (CS). Não houve feito sobre o pH, butirato e N amoniacal, mas todos tratamentos diminuíram a concentração total de ácidos graxos de cadeia curta. MON e MON+LEV reduziram acetato (%) e a relação acetato:propionato. O propionato aumentou com MON e MON+LEV e com LEV nos tempos 4 e 6 horas após a alimentação. LEV aumentou o número de protozoários enquanto que MON e MON+LEV os inibiram. Não houve efeitos de LEV e MON+LEV sobre a degradação in situ de nenhum dos alimentos avaliados, porém a monensina aumentou a taxa de degradação do FDN da CS. Os efeitos da monensina sobre a fermentação ruminal são mais significantes do que aqueles observados com leveduras, e a combinação de ambos os aditivos não potencializa os resultados.